2023
DOI: 10.1186/s12889-023-16447-4
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin D deficiency and lipid profiles in overweight and obese adults: a systematic review and meta-analysis

Xiao Huang,
Yan Yang,
Yingling Jiang
et al.

Abstract: Objective The association between vitamin D deficiency and lipid profiles in adults with overweight or obesity remains unclear and inconsistent. The aim of our study was to determine the relationship between lipid profiles and vitamin D deficiency in the overweight and obese adults. Methods Four databases, including PubMed, the Web of Science, EMBASE and the Cochrane Library, were used to identify all studies on vitamin D status and lipid levels, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…A meta-analysis including a total of 55 observational studies demonstrated that vitamin D levels were negatively associated with BMI both in diabetic and non-diabetic subjects, while a more significant correlation was seen in the diabetic subject population [ 25 ]. Furthermore, several studies suggested that increasing vitamin D levels could help improve the lipid profile of adolescents or children, and vitamin D deficiency may impair the lipid profile of adults [ 26 , 27 ]. While multiple studies have found a negative correlation between vitamin D levels and obesity, the direction of this relationship has remained a subject of controversy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis including a total of 55 observational studies demonstrated that vitamin D levels were negatively associated with BMI both in diabetic and non-diabetic subjects, while a more significant correlation was seen in the diabetic subject population [ 25 ]. Furthermore, several studies suggested that increasing vitamin D levels could help improve the lipid profile of adolescents or children, and vitamin D deficiency may impair the lipid profile of adults [ 26 , 27 ]. While multiple studies have found a negative correlation between vitamin D levels and obesity, the direction of this relationship has remained a subject of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have explored vitamin D status concerning obesity and found an inverse relationship between vitamin D levels and BMI [ 23 , 24 , 25 ]. A recent meta-analysis suggested that vitamin D deficiency was associated with impaired lipid profiles among adults with overweight or obesity [ 26 ]. The study in children and adolescents showed similar results [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the lack of impact is consistent with findings from studies administering doses of 1600–2000 IU/day [ 15 , 25 ]. Intriguingly, within our subgroup analysis, women with persistent 25OHD insufficiency demonstrated a nuanced effect, showcasing lower HDL-C levels in the intervention group compared to the control counterparts, likely due to metabolite interactions, such as with leptin [ 42 ]. An increase in vitamin D level following supplementation has been shown to increase leptin levels [ 42 ], which has been reported to be inversely correlated with HDL-C levels [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, within our subgroup analysis, women with persistent 25OHD insufficiency demonstrated a nuanced effect, showcasing lower HDL-C levels in the intervention group compared to the control counterparts, likely due to metabolite interactions, such as with leptin [ 42 ]. An increase in vitamin D level following supplementation has been shown to increase leptin levels [ 42 ], which has been reported to be inversely correlated with HDL-C levels [ 43 ]. Hence, further investigation into potential metabolite interactions may explain the lower HDL-C levels in our intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, the link between obesity and vitamin deficiency has been discussed and reviewed in the literature for a long time. 5,6 Vitamins represent a group of biologically active compounds that exert multiple functions in maintaining normal of the human body. Vitamin deficiency is common in people suffering from obesity, which may be linked to the involvement of vitamins in antioxidant, redox, and anti-inflammatory processes.…”
Section: Introductionmentioning
confidence: 99%